Exploring the Use of ChatGPT as a Writing Assistant for EFL Students: Opportunities and Pedagogical Implications - Anis Setiyanti (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2024)
The rapid development of artificial intelligence (AI), particularly generative tools such as ChatGPT, has significantly influenced language education, offering new possibilities for supporting English as a Foreign Language (EFL) writing instruction. This study explores the use of ChatGPT as a writing assistant among undergraduate EFL students, focusing on its impact on writing performance, learner perceptions, and pedagogical implications. A mixed-method design was employed, combining quantitative and qualitative approaches to obtain comprehensive insights. Forty EFL students enrolled in an academic writing course at an Indonesian public university participated in a six-week intervention. Quantitative data were collected through pre-test and post-test writing assessments and perception questionnaires, while qualitative data were obtained through semi-structured interviews. The findings indicate statistically significant improvements in students’ writing performance across content, organization, vocabulary, grammar, and coherence, with the most notable gains observed in grammatical accuracy and textual coherence. Students reported positive perceptions of ChatGPT, highlighting its usefulness for idea generation, vocabulary enhancement, and immediate feedback, which increased motivation and writing confidence. Qualitative data further revealed that ChatGPT functioned as an accessible learning companion that supported autonomous learning and reduced writing anxiety. However, challenges were also identified, including overreliance on AI-generated content, reduced critical engagement, and ethical concerns related to plagiarism and academic integrity. These findings suggest that while ChatGPT offers substantial benefits as a complementary writing tool, its integration requires careful pedagogical guidance, AI literacy education, and clear ethical policies. Overall, this study underscores the potential of AI-assisted writing tools to enhance EFL writing instruction while emphasizing the importance of balanced, responsible implementation in educational contexts.